Arcobacter (Campylobacter) butzleri-associated diarrheal illness in a nonhuman primate population. - Anderson, K F (1993)
After DNA hybridization identified an isolate from an ill rhesus macaque (Macaca mulatta) as Arcobacter (Campylobacter) butzleri, we initiated a study to determine whether A. butzleri was associated with diarrheal disease in nonhuman primates at the Yerkes Primate Research Center. By using Campy-CVA medium incubated at 35 degrees C, 15 A. butzleri isolates were obtained from 14 macaques; 7 macaques were coinfected with Campylobacter coli and Campylobacter jejuni. A. butzleri was not isolated from normal feces, despite the fact that feces from 76 macaques were cultured at necropsy. Histologic evaluation of colonic specimens from three macaques from which A. butzleri had been isolated showed mild to moderately severe chronic, active colitis. Ribotype analysis of the 15 A. butzleri isolates revealed nine different strains; these data suggest that A. butzleri may be endemic in this primate population and that a point source of infection is unlikely. This is the first report of the presence of A. butzleri in juvenile and adult macaques with diarrhea, and it may present an opportunity to study the pathogenesis of this organism, which appears to be associated with persistent diarrhea in humans.